Predictor's Factors of Mortality of Patients Suffering from Severe Head Injury in Emergency Department at General Hospital Tugurejo Semarang - Mugi Hartoyo; Sarkum Setyo Raharjo; Budiyati Budiyati (Poltekkes Kemenkes Semarang, 2012)
This research is a descriptive correlation study with cross sectional design to search the relation factors affecting mortality among severe head injury patients. Data of the study was collected from medical record of patients suffering from severe head injury who admitted at energency department of Tugurejo general hospital Semarang during Nopember 2010 until Oktober 2011. From 57 respondents, 19 people passed away during obtaining treatment at emergency department. There were three factors related to mortality of severe head injury patients. Theese were blood pressure on emergency department (ED) admission (p = 0,000), GCS on admission (p = 0,000), and Injury Severity Score (ISS) (p = 0,000). The logistic regression biner resulted that there were no dominant factors related to mortality of severe head injury patients (p more than 0,05). The odd ration of blood pressure variable is the hightes (0,688) compare to other variables such as GCS (OR = 0,281) and ISS (0,594).